Media Pembelajaran Fingerspelling Alphabet untuk Penderita Tunarungu dan Tunawicara Berbasis Android - Mirfan, Mirfan (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2021)
Fingerspelling is one of sign language by using the, hands lips or body to symbolize vocabularyindonesia.penelitian language is aimed at: to design and implement media applicationsfingerspelling learning the alphabet to people with the deaf and tunawicara an android.Datacollection in this research, obtained through a technique, observation interviews andengineering. literatureA design study that used is the unified modeling language uml ( ), whichis designed in a structured consisting of a draft model usecase, diagram activity, diagramsequence diagram. diagrams and classThe software used in building this system is theapplication unity. System was featuring sign language fingers spelling accompanied withimages and explanation for each gambar.dan can be used to help of society especially patientstunawicara in berkomunikasi.terdapat menu evaluation to evaluate lessons material that hasread or seen in menu the finger spelling alphabetic and menus conversation basic the fingerspelling .The understanding of users can known , how far our insights about sign language thefinger spelling